Data from: The history and range expansion of peregrine falcons in the Thule area, northwest Greenland - Burnham, Kurt K. (Movebank Data Repository, 2020)
Burnham KK, Burnham WA, Newton I, Johnson JA, Gosler AG (2012) The history and range expansion of peregrine falcons in the Thule area, northwest Greenland. Bioscience 60, Monographs on Greenland subseries 353. Museum Tusculanum Press, Copenhagen. 106 p. ISBN: 9788763539005 : Peregrine Falcons, Falco peregrinus tundrius, were historically unknown to Inuit and early explorers in the Pituffik (Thule) area, northwest Greenland (75.90–77.60° N). Here we provide information collected from 1993–2005 on what we believe is a recently established and expanding population of High Arctic nesting Peregrines in the area associated with climate change. From 1979 to 2005, the average of the mean monthly temperature, minimum monthly temperature, and maximum monthly temperature for the five-month period, May through September, increased 1.1, 0.5, and 1.6 °C, respectively. Forty-one breeding attempts were recorded at six sites from 1993 to 2005 for this new population. Satellite transmitters were used to determine the home ranges and seasonal movements of female Peregrines, with adults traveling an average of 10,794 km at a rate of 205 km/day on outward migration. During outward migration, the maximum distance traveled by any female on one day was 1,349 km with the maximum total outward and return migrations for single individuals 12,438 and 11,071 km, respectively, to and from south America. Comparisons with Peregrine populations in Greenland at 67° N and 60.5° N, approximately 1,100 (Kangerlussuaq) and 1,700 (south Greenland) km south of the Pituffik area, respectively, show differences in various aspects of ecology. Based on a lack of both morphological and genetic differences it appears the Pituffik area population is likely a result of the extension of more southern breeding Peregrines moving north and taking advantage of an ameliorating climate and lengthened breeding window. Should climatic amelioration continue, the species may eventually expand its range into the very northernmost land area, Peary Land.